Gaps and Challenges in Child Marriage Regulation: An Indonesian and Australian Legal Perspective - Imron Rosyadi; Muchlis Muchlis; Tajul Arifin; Ahmad Fathoni; Fahadil Amin Al Hasan (Justicia Islamica, 2025)
Child marriage remains a persistent global issue, including in Indonesia and Australia. Despite legal frameworks that set a minimum age for marriage, the practice persists due to loopholes, socio-cultural factors, and weak enforcement. This study adopts a comparative legal approach by analysing statutory regulations, court decisions, and relevant academic literature within the contexts of Islamic law, Indonesian law, and Australian law. Findings reveal that the challenges in regulating child marriage are not purely juridical but are significantly influenced by psychosocial conditions. In Indonesia, the prevalence of marriage dispensations and cultural norms that tolerate early marriage creates a tension between legal norms and social realities. In contrast, Australia, while having a stronger legal framework and a relatively low prevalence, still allows dispensations for those aged 16–17 and faces cases of forced marriage within migrant communities, compounded by limited national data. The study’s contribution lies in demonstrating the importance of a legal-psychosocial perspective for understanding and addressing child marriage regulation. Protecting children’s rights, therefore, requires not only normative reforms but also comprehensive social interventions that address underlying cultural and structural drivers.